Pullout strength of all-suture and metallic anchors in repair of lateral collateral ligament injuries of the elbow - Midtgaard, Kaare S.; Nolte, Philip-Christian; Miles, Jon W.; Tanghe, Kira K.; Douglass, Brenton W.; Peebles, Liam A.; Provencher, Matthew T. (Arthroscopy, 2021)
Purpose - To compare the biomechanical properties of metallic anchor (MA) and all-suture anchor (ASA) constructs in the anatomic reattachment of the lateral ulnar collateral ligament complex to its humeral insertion. - Methods - Twenty paired male human cadaveric elbows with a mean age of 46.3 years (range: 33-58 years) were used in this study. Each pair was randomly allocated across 2 groups of either MA or ASA. A single 3.5-mm MA or 2.6-mm ASA was then inserted flush into the lateral epicondyle. A dynamic tensile testing machine was used to perform cyclic loading followed by a load to failure test. During the cyclic loading phase, the anchors were sinusoidally tensioned from 10 N to 100 N for 1,000 cycles at a frequency of 0.5 Hz. In the load to failure test, the anchors were pulled at a rate of 3 mm/s. Load at 1-mm and 2-mm displacement, as well as load to ultimate failure were assessed. Clinical failure was defined as displacement of more than 2 mm. Normality of data was assessed with the Shapiro-Wilk test. Continuous data are presented as medians and compared with the Mann-Whitney U test and categorical data was compared with the χ2 test or Fisher exact test. - Results - Displacement was significantly greater for the ASA group during cyclic loading starting from the tenth cycle (P < .05). Displacement of more than 5 mm within the first 100 cycles was observed in 2 anchors in the ASA group. No difference was observed in loads required to displace 1 mm (MA: 146 N [6-169] vs ASA: 144 N [2-153]; P = .53) and 2 mm (MA: 171 N [13-202] vs ASA: 161 N [9-191]; P = .97), but there was a statistically significant difference between ultimate loads in favor of ASA in the load to failure test (MA: 297 N [84-343] vs 463 N [176-620]; P < .01). - Conclusions - In the cyclic test, no difference in clinical failure defined as pull-out of more than 2 mm was observed between 3.5 mm MAs and 2.6 mm ASAs. In the ultimate load to failure analysis, no difference was observed between groups in force causing 1 and 2 mm of displacement, but there was a significant difference in favor of ASA in the pull to ultimate failure test. - Clinical Relevance - Potential benefits of all-suture anchors include preservation of bone stock, reduced radiographic artifacts, and easier revisions. Although their use has been investigated thoroughly in the shoulder, there remains a paucity of literature regarding displacement and pull-out strength in the elbow.
Gesehen am 16.09.2022